PROTOTIPE SISTEM INFORMASI TUNTUNAN PERJALANAN WISATA DI PROVINSI BALI - Suputra, Putu Gede Hendra (JISA(Jurnal Informatika dan Sains), 2018)
E-Tourism is a digital platform that connects all tourism stakeholders, and integrates all tourism activities and makes it easy for all travelers to explore tourism charms by accessing applications without being tied to places and times. In Indonesia especially in Bali the development of E-Tourism can be very good. Many sites are available on the internet to be a medium of information and tourist accommodations booking media. In addition, many government and private sites also play a role in the process of providing tourist information, but these sites can be said to be static and simple. These providers only provide text information without prioritizing responsiveness and interactivity to the users.Responsiveness and interactivity are two issues in today's tourism sites. The existing tourism sites in Indonesia are still lacking in responding to the needs or questions of the users and also the interactive functions on the site are felt to be less than satisfactory. Users are only provided an information in the form of photographs and writings about a tourist attraction. Users never know where places can be visited with approximate time, location recommendations, routes and schedules that adjust to user needs. Refers to the problems,we develop an application that able to give recommendation and guidance of tour in Bali area.The system is made on the main needs that have been defined that the system is able to provide travel recommendations. After testing with black box model, the result of the system has been able to meet the needs of the user and provide travel recommendations in accordance with the needs of the user where the travel time-limited, category of place, place of the beginning of the journey and the final place has been fulfilled. The system has given the suitable recommendations based on the criteria that the user wants.